2017
DOI: 10.1136/bmjdrc-2017-000408
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity to spatial gratings in moderate and dim light conditions in patients with diabetes in the absence of diabetic retinopathy

Abstract: ObjectiveTo evaluate the ability of contrast sensitivity (CS) to discriminate loss of visual function in diabetic subjects with no clinical signs of retinopathy relative to that of normal subjects.Research design and methodsIn this prospective cross-sectional study, we measured CS in 46 diabetic subjects with a mean age of 48±6 years, a best-corrected visual acuity of 20/20 and no signs of diabetic retinopathy. The CS in these subjects was compared with CS measurements in 46 normal control subjects at four spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…A further experiment (Experiment 3), aimed at measuring a range of illumination intensities in mesopic light condition confirmed results obtained in Experiment 2 and showed that values above 125 lux did induce a significant decrease of the CSF. Taken together, the present results suggest that, while glare-induced reduction of the CSF can be achieved with currently available systems in clinical populations, i.e., astigmatism patients who underwent LASIK surgery ( Safi et al, 2017 ), in order to successfully reduce the CSF in young healthy individuals it is necessary to use a luminance level that the currently available standard CS tests do not reach (125 lux).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A further experiment (Experiment 3), aimed at measuring a range of illumination intensities in mesopic light condition confirmed results obtained in Experiment 2 and showed that values above 125 lux did induce a significant decrease of the CSF. Taken together, the present results suggest that, while glare-induced reduction of the CSF can be achieved with currently available systems in clinical populations, i.e., astigmatism patients who underwent LASIK surgery ( Safi et al, 2017 ), in order to successfully reduce the CSF in young healthy individuals it is necessary to use a luminance level that the currently available standard CS tests do not reach (125 lux).…”
Section: Discussionmentioning
confidence: 74%
“…Nonetheless, future studies should also assess whether the photopic CSF can be similarly affected by extremely high levels of glare in young healthy individuals. This would provide an additional valuable piece of information since Safi et al (2017) showed that comparing CS measured in different light conditions produces a more accurate classification of diabetic patients with no retinopathy from normal sighted individuals respect to the CS measured under a single light condition; similarly, comparing mesopic and photopic CS with glare might reveal subtle differences that might be lost in a single light condition test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a group of vision researchers have shown that CS, a measure of the ability of an individual to discriminate among different shades of gray, is a more sensitive tool to detect the early retinal changes and distinguish different diabetic subgroups than VA ( Dosso et al., 1998 ; Abrishami et al., 2007 ; McAnany et al., 2019 ). A study by Safi et al. (2017) showed that patients with diabetes (without any clinical signs of retinopathy) exhibited a uniform loss in CS at different special frequencies like 3, 6, 12, and 18 cycles/degree.…”
Section: Introductionmentioning
confidence: 99%
“…24 , 25 Studies have shown that even in diabetic patients with good VA, CS could be impaired. 26 28 CS is thus an important outcome measure and could be considered as an adjunct to standard VA testing for a more complete assessment of visual function in DME patients. The CS test has been proven useful for diagnosing early and advanced DR. 24 , 26 , 29 It has also grown in popularity as a clinical tool for evaluating the impact of therapy since potential treatment response may not be completely characterized by VA measurement alone.…”
Section: Introductionmentioning
confidence: 99%